El Museo Municipal de música popular de Julio Jaramillo como atractivo turístico de la ciudad de Guayaquil - Acosta Echeverria, Jordy Wladimir (2022)
The present investigation consists of recommending the Julio Jaramillo popular music museum as a tourist attraction in the city of Guayaquil in order to potentiate the visits of national and foreign tourists. This project was born from observing the disinterest and cultural ignorance of an emblematic place, heritage and symbol of our national history. During the investigative process, the study variables were investigated in depth, in addition, different research methods were applied, such as: the deductive, inductive, analytical and descriptive method, which contributed to the development of my study. Likewise, the survey technique is used, which aims to collect information from tourists who visit the museum, in this way it will be possible to identify detected situations and then give them a solution from a professional approach. Finally, with the results obtained through this process, the need to recommend the museum as a tourist attraction of cultural importance is identified, from the professional field it is suggested the promotion of this attraction through advertising in digital media and social networks since currently the Most of the population uses this type of tools.